Description of Antho (Plocamia) bremecae sp. nov. and checklist of Microcionidae (Demospongiae: Poecilosclerida) from Burdwood Bank and neighboring areas, SW Atlantic Ocean - Schejter, Laura; Bertolino, Marco; Calcinai, Barbara (Zootaxa)
In this contribution, we describe a new Demospongiae species, Antho (Plocamia) bremecae sp. nov., from the west slope of Burdwood bank, a poorly studied region in the SW Atlantic Ocean. We also recorded for the first time in the region two other microcionid species, Clathria (Axosuberites) nidificata and Clathria (Microciona) antarctica. In addition, a regional checklist of Microcionidae from Burdwood Bank and neighboring areas, including Malvinas (Falkland) Islands, Tierra del Fuego Province and the North of the Scotia Arc (South Georgia and Shag Rocks) is provided. Fil: Schejter, Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Subsede Instituto Nacional de Investigación y Desarrollo Pesquero; Argentina Fil: Bertolino, Marco. Universitá di Genova; Italia Fil: Calcinai, Barbara. Universita Politecnica Delle Marche; Italia